WET MECHANICAL SEAL RELIABILITY IMPROVEMENTS - Ariyanto, Ariyanto (Universitas Gunadarma, 2016)
Mechanical seal is a major component of the fluid transport system as an insulation to prevent fluid leakage in pump. Wet mechanical seal as components used working fluid passing through a shaft and serves to hold the fluid pressure and friction. PT. Wilmar Nabati Gresik Indonesia is one customer Johncrane that have data seal installation and components failure of the wet mechanical seal during 33 months (2012 – 2014). Analyses quantitatively by mathematical calculation reliability of components to reliability improvements. The greatest failure component of the mechanical seal are o - ring seals (77,13%) and bellows seal (20,63%). Reliability of mechanical sealswas in conﬁdence limits range 97% - 99 %. The investment required to achieve higher reliability should be off set against the benefit when deciding on the most suitable plan of recommendation actions. Identifying the cause of failure, addressing the problems using defect elimination techniques, cost benefit analysis can be carried out to justify the time and costsassociated with reliability improvement. Keywords:Wet mechanical seal, Reliability, Improvements